2018
DOI: 10.13057/nusbiosci/n100408
|View full text |Cite
|
Sign up to set email alerts
|

The role of neem leaves as organic pesticides in chili pepper (Capsicum frutescens)

Abstract: Sopialena, Sila S, Rosfiansyah, Nurdiana J. 2018. The role of neem leaves as organic pesticides in chili pepper (Capsicum frutescens). Nusantara Bioscience 10: 246-250. The agricultural crops and horticultural plants are always under constant assault caused by diseases, insect pests, viruses, and other pathogens which may substantially reduce yield. Chili Pepper (Capsicum annum L.) is a popular horticultural plant of the Solanaceae family in Indonesia. Some serious diseases widely found in chili peppers, are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…Aspergillus flavus penghasil aflatoksin pada tanaman kedelai (Krishnamurthy dan Shashikala 2006). Aplikasi ekstrak daun mimba pada pertanaman cabai berpengaruh signifikan terhadap produksi buah per hektar dan efektif mengurangi infeksi penyakit antraknosa (Sopialena et al 2018). Pada sebuah uji pendahuluan diketahui bahwa formulasi ekstrak dari tanaman mimba dengan bahan aktif azadirachtin, salanin dan nimbin mampu menghambat pertumbuhan Fusarium oxysporum, penyebab penyakit busuk pangkal pada bawang bombay (Krishanti dan Prianto 2016) dan meningkatkan aktivitas antifeedant azadirachtin terhadap S. litura (Prianto 2019).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Aspergillus flavus penghasil aflatoksin pada tanaman kedelai (Krishnamurthy dan Shashikala 2006). Aplikasi ekstrak daun mimba pada pertanaman cabai berpengaruh signifikan terhadap produksi buah per hektar dan efektif mengurangi infeksi penyakit antraknosa (Sopialena et al 2018). Pada sebuah uji pendahuluan diketahui bahwa formulasi ekstrak dari tanaman mimba dengan bahan aktif azadirachtin, salanin dan nimbin mampu menghambat pertumbuhan Fusarium oxysporum, penyebab penyakit busuk pangkal pada bawang bombay (Krishanti dan Prianto 2016) dan meningkatkan aktivitas antifeedant azadirachtin terhadap S. litura (Prianto 2019).…”
Section: Pendahuluanunclassified
“…Seperti yang dilakukan oleh Ali et al (2012), yaitu merendam buah cabai tanpa dilukai sehingga ekstrak mimba mampu mengendalikan cendawan patogen yang berada di permukaan buah cabai dan menurunkan keparahan penyakit. Aplikasik ekstrak mimba pada 59, 66, 73, 80, 87, dan 94 hari setelah tanam efektif menurunkan keparahan penyakit antraknosa pada pertanaman cabai (Sopialena et al 2018). Penggunaan ekstrak mimba dengan interval 15 hari mampu mengurangi tanaman dan buah yang terinfeksi oleh C. capsici (Rashid et al 2015).…”
Section: Pembahasanunclassified
“…In an experiment the botanicals or plant extracts from Catharanthus roseus, Coleus aromaticus, Manilka razapota and A. indica used against fungi, it was concluded that these botanicals confer antifungal effects on the radial mycelial growth of C. truncatum [107]. The organic pesticides were prepared from the extract of neem leaves, soursop leaves, lemongrass extract, tuba root extract, and kenikir/Cosmos caudate extract [110]. The result indicates that neem leaves are the most effective organic pesticides to control the chilli pepper disease especially in Indonesia.…”
Section: Plant Extractsmentioning
confidence: 99%
“…From the existing land area, most of them have been used the paddy varieties such as Ciherang, Cimelati, and Mekongga (Susilastuti 2018). Though the use of plantbased pesticides is common among farmers (Sopialena et al 2018b), the pathogenic microorganisms seem to be potential problems still. In this regard, this study found that Pandan Ungu variety is rarely used due to its susceptible characteristics to pathogens.…”
Section: Introductionmentioning
confidence: 99%